In Vitro Evaluation of Brown Algae Extract from Sargassum aquifolium in Inhibiting Aeromonas hydrophila, the Causative Agent of Motile Aeromonas Septicemia (MAS) - Ernawati Waruwu; Anak Agung Ayu Putri Permatasari; Putu Angga Wiradana; I Made Wisnu Adhi Putra; Putu Eka Sudaryatma; Muhammad Khaliim Jati Kusala (Journal of Aquaculture Science, 2024)
The widespread use of antibiotics in aquaculture has been associated with the development of multidrug resistance in the environment and in humans. This is also exacerbated by the application of high stocking densities in fish farming systems, including catfish (Clarias sp). This study aims to see the potential of Sargassum aquifolium extract, which is a brown macroalgae, as an antibacterial agent for fish disease, Aeromonas hydrophila. Previous studies have revealed the phytochemical profile of S. aquifolium extract, but its effectiveness as an antibacterial agent has not been studied. The ethanol extract concentrations used were 20%, 40%, 60%, 80%, and 100% with two repetitions. The MIC test method was carried out to determine the lowest concentration of S. aquifolium ethanol extract that could inhibit the growth of Aeromonas hydrophila bacteria, while the MBC test was carried out to determine the bactericidal properties against A. hydrophila bacteria. SEM analysis was carried out to determine the morphological damage to A. hydrophila bacterial cells that had been treated with S. aquifolium ethanol extract. Based on the results, it was revealed that S. aquifolium extract could inhibit the growth of A. hydrophila highest with a very strong category at a concentration of 100%. The MIC value of S. auifolium extract was shown at a concentration of 100% but did not cause bacterial cell death based on the MBC value and SEM observations. These findings indicate that S. aquifolium extract has the potential to inhibit the growth of A. hydrophila. Increasing in vivo parameters such as the immune system, production performance, and survival in catfish is still needed to strengthen these results.